2009
DOI: 10.1590/s1516-18462009000600007
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinaridade na fonoaudiologia: a concepção do professor

Abstract: RESUMOObjetivo: analisar a concepção de interdisciplinaridade referida pelos professores fonoaudiólogos do curso de Fonoaudiologia da Universidade do Vale do Itajaí. Métodos: a pesquisa orientou-se por uma abordagem qualitativa através da Análise do Discurso de Linha Francesa, tendo como instrumento de coleta de dados a entrevista em profundidade. Resultados: após a análise, identificaram-se diferentes posições sujeito, onde se podem observar a concepção e o conhecimento sobre a interdisciplinaridade, as possí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(22 reference statements)
0
3
0
1
Order By: Relevance
“…It is notorious that the vocal care is not restricted to the clinic, but involves other aspects that deal with the expressiveness in singing and public speaking, for example. The difficulty in achieving interprofessional practices routinely requires investments in studies about the subject and, in such cases, specifically, about the training of health professionals (24) . An example that can be highlighted is the formation of chorus in Basic Health Units, which often begins with the initiative of community workers and ultimately involves different health professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is notorious that the vocal care is not restricted to the clinic, but involves other aspects that deal with the expressiveness in singing and public speaking, for example. The difficulty in achieving interprofessional practices routinely requires investments in studies about the subject and, in such cases, specifically, about the training of health professionals (24) . An example that can be highlighted is the formation of chorus in Basic Health Units, which often begins with the initiative of community workers and ultimately involves different health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…This work provides the exchange of experiences and the construction of goals together, factors that lead to the better care of those who seek those professionals, as well as better professional training 24 . Although the educational institutions should be alert to the need of preparing different professionals to this joint action, as recommended by the current healthcare system in the country, much still lies ahead.…”
Section: Discussionmentioning
confidence: 99%
“…A interdisciplinaridade aparece para promover a superação da superespecialização e da desarticulação entre teoria e prática 23 .…”
Section: Inclusão Do Trabalho Em Equipes Multidisciplinares Principaunclassified
“…Results demonstrated that the a better development of second language seems to be associated to the early exposure to the second language because in the first infancy there is still a great plasticity of auditory skills and the discrimination of phonemes is not restrict indicating that the formal teaching of second language and the perceptual skills should be stimulated at this age range. 10,11 . Then, we performed exhaustive and fluctuating reading of data, trying to analyze what had repeated in the speech of the patient.…”
Section: Introductionmentioning
confidence: 99%